E4orf1 as a key modulator in oncogenesis and of metabolism in Adenovirus infection - Hernández-Magaña, Leidy Erandy; Mosqueda-Gracida, Alfredo; Cruz-Holguín, Víctor Javier; Martínez-Castillo, Macario; Fuentes-Pananá, Ezequiel M.; Rozmyslowicz, Tomasz; León-Juárez, Moisés; Arévalo-Romero, Haruki (Frontiers in Virology, 2023)
Human Adenoviruses are a diverse family of viruses that can infect a variety of tissues causing acute or persistent infection. Viruses induce numerous cellular alterations as they hijack cellular functions to promote viral progeny. Recent research has shed light on the functions of viral proteins in orchestrating viral production, revealing that many of these functions overlap with oncogenesis or metabolic disruption. Studies of the Adenovirus family (Adenoviridae) have identified oncogenic members, such as Adenovirus (Ad-)2, 5, 9, and 12, and also Ad-36, which is most extensively studied for its ability to induce metabolic alterations. Specifically, Adenoviruses encode a gene product known as early region 4 open reading frame 1 (E4orf1), which has emerged as an oncoprotein and regulator of metabolism depending on the lineage of the infected host cell. This article aims to provide insight into the functions of the viral protein E4orf1 and the overlapping similarities between the oncogenic process and cell metabolism.